Daily Stress Symptoms, Sources of Stress and Stages of Change for Stress Management in Primary and Secondary School Children - Kamtsios Σπυρίδων; Digelidis Νικόλαος (Inquiries in Physical Education and Sport, 2008)
The purpose of the study was to identify the daily sources of stress in primary and secondary school children, their physical and psychological stress symptoms and their stages of change for stress management. The research took place in two periods. In the first one ninety pupils were interviewed and their perceived sources of stress were presented in three levels: daily stress, school stress and stress in physical education lesson. The second period of the research (300 pupils participated), was held through questionnaires reporting stress sources and symptoms. Internal consistency and factorial validity provide preliminary support for the psychometric properties of the stress sources questionnaire, which constitute from three factors and 25 questions. From the results it was found out that school, generally, is a major source of stress. It was also found that high school children reported more physical and psychological stress symptoms, while few children adopt strategies for coping with stress reflecting awareness of stress symptoms, as well as, the corresponding stages of behaviour change. The results of the study imply the need of the reinforcement of health education and the implementation through physical education lesson, in order to strengthen the students’ coping skills.